Macroelement water-soluble fertilizer and preparation method thereof
By introducing iron metal organic frame materials and composite biochar materials into water-soluble fertilizers, the problems of nitrate nitrogen pollution and low nitrogen utilization in traditional fertilizers are solved, and the effect of efficient supply of crop nitrogen, optimizing the soil environment and improving crop growth performance is achieved.
Patent Information
- Application Number
- CN202510010112.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional large amounts of elemental water-soluble fertilizers cause nitrate nitrogen pollution in soil and groundwater during use, and the nitrogen utilization rate is low, making it difficult to meet the nitrogen needs of crops at different growth stages.
A large amount of elemental water-soluble fertilizer made of tripopotassium phosphate, potassium dihydrogen phosphate, sodium octaborate tetrahydrogen sulfate, zinc sulfate monohydrate, water, and composite biochar materials is used to convert nitrate nitrogen into ammonium nitrogen through iron metal organic framework materials, and the pore structure of composite biochar materials is used to achieve sustained release of nutrients.
This fertilizer can efficiently supply crop nitrogen, improve nitrogen utilization, reduce soil and groundwater pollution, optimize soil structure and microbial environment, and enhance crop stress resistance and growth performance.
Smart Images

Figure BDA0005228126390000271 
Figure BDA0005228126390000281 
Figure BDA0005228126390000282
Abstract
Description
Technical Field
[0001] The invention relates to the field of fertilizers, and in particular to a macro-element water-soluble fertilizer and a preparation method thereof. Background Art
[0002] Modern agricultural development faces complex challenges. With the continuous growth of the global population, the demand for food continues to rise. In order to ensure crop yields, a large number of water-soluble fertilizers are widely used, resulting in a continuous increase in market demand. With its significant advantages such as rapid absorption and utilization by crops and flexible and diverse fertilization methods, water-soluble fertilizers have occupied an increasingly critical position in the process of agricultural refinement and intensive development, showing broad application prospects.
[0003] On the one hand, facility agriculture is booming, and modern planting models such as greenhouses and soilless cultivation have put forward higher requirements for the water solubility and quick-acting properties of fertilizers. Water-soluble fertilizers can be accurately applied through drip irrigation and sprinkler irrigation systems, which meets the needs of precision management of facility agriculture. They can supply nutrients in time at key points of crop growth, greatly improve resource utilization efficiency, reduce fertilizer waste and soil pollution, and provide solid guarantees for the year-round supply and quality optimization of agricultural products. The market share is expected to continue to expand.
[0004] On the other hand, as consumers pay more and more attention to the quality and safety of agricultural products, green and organic agriculture has gradually become the mainstream trend. High-quality water-soluble fertilizers contain no or very little heavy metals, hormones and other harmful substances, which can help produce high-quality agricultural products that are nutritious, delicious, and have pesticide residues that meet standards. They meet high-end market and export standards, have strong competitiveness in domestic and foreign markets, and have huge development potential.
[0005] However, traditional macronutrient water-soluble fertilizers have many drawbacks. From the perspective of soil ecology, nitrogen in fertilizers is rapidly converted into nitrate nitrogen (NO3 - -N). During irrigation, nitrate nitrogen migrates underground with water through soil pores, causing nitrate pollution in groundwater, which seriously threatens drinking water safety. This is because soil particles have limited adsorption capacity for nitrate nitrogen. Under hydraulic drive, nitrate nitrogen easily leaves the soil adsorption site and enters groundwater.
[0006] In terms of crop nutrition, different crops have different requirements for nitrogen forms. For example, the roots of cereal crops such as rice require ammonium nitrogen (NH4 + -N) has a strong affinity and high absorption efficiency; however, the nitrogen release form and rate of conventional fertilizers are difficult to match the needs of crops at specific growth stages. A large amount of nitrate nitrogen cannot be used efficiently and is lost, resulting in a low nitrogen utilization rate, usually only 30%-40%, which not only wastes resources and increases costs, but also aggravates environmental pollution of soil and water bodies, such as soil acidification, water eutrophication and other ecological problems.
[0007] In this case, biochar materials and metal-organic framework materials bring new opportunities. Biochar is made from agricultural and forestry wastes through high-temperature oxygen-limited pyrolysis. It is porous inside, has a large specific surface area, and is rich in functional groups such as carboxyl and phenolic hydroxyl groups. These characteristics enable it to adsorb nutrients from soil solution and reduce leaching; it can adjust soil pH through ion exchange, improve soil structure, increase porosity and water and fertilizer retention capacity, and facilitate the survival and reproduction of microorganisms. Metal-organic framework materials are chemically synthesized to have a regular crystal structure, a high specific surface area, and a precisely controllable pore size, and the iron active sites are highly active. In the field of fertilizers, its pores can adsorb nutrients to achieve slow release; for nitrate nitrogen, it can use electronic structure and confinement effect to catalytically reduce it to ammonium nitrogen, providing a feasible path for the innovation of traditional fertilizers. The integration of the two in the formulation of large-element water-soluble fertilizers is of great research and application value.
[0008] Therefore, according to the above-mentioned related technologies, it is urgent to develop a large amount of element water-soluble fertilizer and a preparation method thereof. Summary of the invention
[0009] In view of this, the purpose of the present invention is to propose a macro-element water-soluble fertilizer and a preparation method thereof, so as to provide a macro-element water-soluble fertilizer formula that integrates efficient fertilizer supply, precise controlled release, soil improvement and eco-friendly characteristics.
[0010] Based on the above purpose, the present invention provides a macro-element water-soluble fertilizer and a preparation method thereof.
[0011] A macro-element water-soluble fertilizer is prepared from the following raw materials in parts by weight: 950-1050 parts of tripotassium phosphate, 75-85 parts of potassium dihydrogen phosphate, 10-12 parts of sodium octaborate tetrahydrate, 1.8-2.2 parts of zinc sulfate monohydrate, 580-620 parts of water, and 50-60 parts of composite biochar material;
[0012] The composite biochar material is prepared from biochar, metal-loaded modified biochar and iron metal material;
[0013] The metal-loaded modified biochar is biochar loaded with iron elements.
[0014] Preferably, the mass ratio of biochar, metal-loaded modified biochar and iron metal material in the composite biochar material is 10-12:25-30:15-18.
[0015] Preferably, the preparation process of the biochar is as follows:
[0016] Step A1. Collect dry crop straw or sawdust, crush to a particle size of 2-5 mm, and take 500-1000 g into the carbonization furnace;
[0017] Step A2. Raise the temperature to 400-600°C at a rate of 5-10°C / min, and pyrolyze for 2-3h in a nitrogen atmosphere (flow rate 20-30mL / min) to fully carbonize the biomass to form a loose porous structure;
[0018] Step A3. After pyrolysis is completed, the product is cooled naturally, and the product is soaked in 1% dilute hydrochloric acid for 2-3 hours to remove ash and alkaline impurities, then rinsed with deionized water until neutral, dried at 100-120°C, ground, and passed through a 100-200 mesh sieve to obtain biochar.
[0019] Preferably, the preparation process of the metal-loaded modified biochar is as follows:
[0020] Grind the biochar into a powder of 200-240 mesh, soak the biochar powder in a ferric nitrate solution, adjust the pH of the system to 9-11 with sodium hydroxide, soak for 8-10 hours, dry at 80-100° C., and calcine at 500-600° C. for 2-4 hours to obtain a loaded metal modified biochar;
[0021] The usage ratio of the biochar to the ferric nitrate solution is 2-2.5 g:8-10 mL, and the concentration of the ferric nitrate solution is 0.3-0.5 mol / L.
[0022] Preferably, the iron metal material includes biochar-modified metal and iron metal organic framework material;
[0023] The mass ratio of the biochar modified metal to the iron metal organic framework in the iron metal material is 6-8:9-10;
[0024] The preparation process of the biochar-modified metal is as follows:
[0025] Step B1. The biomass raw material is crushed at a speed of 2000-3000rpm to ensure the consistency of particle size. If the crushing is uneven, larger particles are prone to incomplete internal carbonization during pyrolysis. The raw material particle size is reduced to 2-5mm to facilitate the subsequent pyrolysis reaction to proceed uniformly, thereby obtaining biomass raw material powder;
[0026] Step B2. Evenly spread the biomass raw material powder in a high-temperature resistant ceramic crucible, and control the filling amount to 55%-65% of the crucible volume to avoid excessive accumulation of materials affecting the escape of pyrolysis gas and the uniformity of heat transfer. Put the crucible filled with biomass raw material powder into the carbonization equipment, close the furnace door, and use nitrogen as a protective gas, and continuously pass it into the furnace at a flow rate of 20-30mL / min to replace the air in the furnace for 15-20min to ensure an oxygen-free environment and prevent the raw material from oxidizing and burning in the early stage of pyrolysis. Subsequently, slowly increase the temperature in the furnace to 400-600°C at a heating rate of 5-8°C / min. At this stage, heating too fast can easily lead to rapid pyrolysis and gas production of biomass, resulting in material splashing and uneven carbonization;
[0027] Step B3. After reaching a predetermined temperature of 400-600°C, the constant temperature is maintained for 2-4 hours to allow the biomass raw material powder to be fully decomposed and transformed under the action of pyrolysis, and the macromolecular structures such as lignin and cellulose are broken and reorganized to form a porous structure rich in carbon. After the constant temperature is completed, the heating is stopped, and the mixture is naturally cooled to room temperature under continuous nitrogen protection. The cooling rate is controlled at 3-5°C / min. Too fast cooling can easily cause the carbon structure to shrink and deform, affecting the development of pores, and thus obtaining biomass carbon powder;
[0028] Step B4. Mix the biomass carbon powder and potassium hydroxide solution evenly to ensure that the biomass carbon powder is fully immersed in the potassium hydroxide solution, transfer the mixture to a polytetrafluoroethylene-lined high-pressure reactor, seal it and place it in an oven, heat it to 700-800°C, and keep it for 100-120 minutes to allow the potassium hydroxide solution and the biomass carbon powder to react chemically at 1.5-2.5MPa, etch the carbon skeleton, and expand the pore structure;
[0029] Step B5. After the reaction is completed, the reactor is cooled naturally to room temperature, and the valve is slowly opened to release the pressure. The product is transferred to an acid-resistant and alkali-resistant container, and repeatedly rinsed with a large amount of deionized water until the pH value of the washing liquid is 6.8-7.2 to remove the residual activator and reaction by-products. The washed carbon powder is then placed in an oven at 100-120°C and dried for 18-22 hours to obtain pretreated biomass carbon powder;
[0030] Step B6. Dissolve ferric nitrate in anhydrous ethanol, add pretreated biomass carbon powder, and ultrasonically disperse for 60-80 minutes at a power of 280-320W and a frequency of 38-42kHz to ensure uniform impregnation of the iron salt. The obtained suspension is evaporated to remove ethanol, and the obtained solid powder is transferred to a tubular furnace, purged with nitrogen for 25-35 minutes at a flow rate of 48-52mL / min, and heated to 830-850℃ at a rate of 8-10℃ / min. The mixture is pyrolyzed at a constant temperature for 100-120 minutes, and the iron atoms are thermally migrated and anchored. After natural cooling, the mixture is pickled with hydrochloric acid at a concentration of 0.08-0.12mol / L for 28-30 minutes, repeatedly rinsed with deionized water until neutral, vacuum dried at 78-80℃ for 10-12h, and ground through a 300-mesh sieve for use to obtain biochar modified metal.
[0031] Preferably, the biomass raw material in step B1 is any one of corn stalks, rice husks and sawdust.
[0032] Preferably, the moisture content of the biomass raw material in step B1 is lower than 15%.
[0033] Preferably, the ratio of the biomass carbon powder to potassium hydroxide in step B4 is 8-10 g: 35-45 mL;
[0034] Preferably, the concentration of the potassium hydroxide solution in step B4 is 4-5 mol / L.
[0035] The usage ratio of ferric nitrate, anhydrous ethanol and pretreated biomass carbon powder in step B6 is 6-8g:180-220mL:8-12g.
[0036] The specific surface area of the pretreated biomass carbon powder in step B6 is 600-800m 2 / g, the pore size of pretreated biomass carbon powder is 2-5nm.
[0037] Preferably, the preparation process of the iron metal organic framework material is as follows:
[0038] Ferric nitrate, ferric chloride and organic ligand are added to a mixed solvent, and after ultrasonic dispersion to make the materials evenly dispersed, they are transferred to a polytetrafluoroethylene-lined reactor, heated to 120-140°C, and reacted continuously for 30-40 hours under mechanical stirring at 180-220r / min. After natural cooling, the suspension is centrifuged at 8000-10000r / min for 20-30 minutes, and the precipitate is collected and alternately rinsed with anhydrous ethanol and deionized water for 4-6 times to completely remove impurities. Finally, it is dried in a vacuum environment at 60-80°C for 16-20 hours, and ground through a 200-300 mesh sieve for use. The nanoscale pores inside the precipitate are crisscrossed, and the iron active sites are scattered. In the scenario of solar-driven or soil in-situ electrochemical reactor, it can efficiently adsorb free NO3 in irrigation water or soil. - -N, with its unique electronic structure and spatial confinement effect, catalytic reduction generates NH4 + -N, can significantly reduce the amount of exogenous nitrogen fertilizer applied, curbing NO3 from the source - -N leakage pollution risk, and obtain iron metal organic framework materials.
[0039] Preferably, the usage ratio of the ferric nitrate, ferric chloride, organic ligand and mixed solvent is 0.18-0.22 mol: 0.1-0.12 mol: 0.25-0.3 mol: 800-900 mL;
[0040] The organic ligand is any one of terephthalic acid and 2-aminoterephthalic acid;
[0041] The mixed solvent is obtained by mixing N,N-dimethylformamide and water in a volume ratio of 675-750:150-225;
[0042] The ultrasonic dispersion has a power of 300-400 W, a frequency of 35-45 kHz, and a time of 40-50 min.
[0043] A method for preparing a macro-element water-soluble fertilizer comprises the following steps:
[0044] Step S1. Put tripotassium phosphate, potassium dihydrogen phosphate, sodium octaborate tetrahydrate and zinc sulfate monohydrate into warm water at 48-52°C, and stir magnetically at a speed of 440-460 r / min for 18-22 min until the solid is completely dissolved to obtain a mixed solution 1;
[0045] Step S2. Add the composite biochar material to the mixed solution 1, stir at 180-220 r / min, and ultrasonically oscillate at a power of 240-260 W and a frequency of 28-32 kHz for 14-16 min to obtain a mixed solution, thereby obtaining a macro-element water-soluble fertilizer.
[0046] Beneficial effects of the present invention:
[0047] The present invention provides a macro-element water-soluble fertilizer and a preparation method thereof. The fertilizer provided by the present invention can realize precise fertilizer supply. The iron metal organic framework material efficiently converts nitrate nitrogen into ammonium nitrogen, and cooperates with macro- and trace elements such as tripotassium phosphate to meet the needs of each stage of the plant and ensure nutrients in the critical period. The pores of the composite biochar material adsorb nutrients to achieve slow release of nutrients, reduce root penetration resistance, enhance stress resistance, reduce growth hindrance, and can also optimize soil aggregates, increase porosity, reduce bulk density, and improve ventilation and water permeability as well as water and fertilizer retention capabilities, which significantly empowers the agricultural economy and greatly increases crop yields. It has broad application prospects. DETAILED DESCRIPTION
[0048] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0049] Embodiment 1: A method for preparing a macronutrient water-soluble fertilizer, comprising the following steps:
[0050] S1. Collect dry crop straw or sawdust, crush to a particle size of 2-5 mm, take 500 g and load into the carbonization furnace;
[0051] S2. The temperature was raised to 400 °C at a rate of 5 °C / min and pyrolyzed for 2 h in a nitrogen atmosphere (flow rate 20 mL / min) to fully carbonize the biomass and form a loose porous structure;
[0052] S3. After the pyrolysis is completed, the product is cooled naturally, and the product is soaked in 1% dilute hydrochloric acid for 2 hours to remove ash and alkaline impurities, then rinsed with deionized water until neutral, dried at 100°C, ground and passed through a 100-mesh sieve to obtain biochar;
[0053] S4. Grind the biochar into a powder of 200-240 mesh, soak 20 g of the biochar powder in 80 mL of 0.3 mol / L ferric nitrate solution, adjust the pH of the system to 9 with sodium hydroxide, soak for 8 h, dry at 80 ° C, and calcine at 500 ° C for 2 h to obtain metal-loaded modified biochar;
[0054] S5. The corn stalks with a moisture content of less than 15% are crushed at a speed of 2000 rpm to ensure the consistency of particle size. If the crushing is uneven, the larger particles are prone to incomplete internal carbonization during pyrolysis. The raw material particle size is reduced to 2-5 mm, which is convenient for the subsequent pyrolysis reaction to proceed uniformly to obtain biomass raw material powder;
[0055] S6. Evenly spread the biomass raw material powder in a high-temperature resistant ceramic crucible, and control the filling amount to 55%-65% of the crucible volume to avoid excessive accumulation of materials affecting the escape of pyrolysis gas and the uniformity of heat transfer. Put the crucible filled with biomass raw material powder into the carbonization equipment, close the furnace door, and use nitrogen as a protective gas, and continuously pass it into the furnace at a flow rate of 20mL / min to replace the air in the furnace for 15min to ensure an oxygen-free environment to prevent the raw materials from oxidizing and burning in the early stage of pyrolysis. Subsequently, slowly increase the furnace temperature to 400°C at a heating rate of 5°C / min. At this stage, heating too fast can easily lead to rapid pyrolysis and gas production of biomass, resulting in material splashing and uneven carbonization;
[0056] S7. After reaching the predetermined temperature of 400°C, the constant temperature is maintained for 2 hours to allow the biomass raw material powder to be fully decomposed and transformed under the action of pyrolysis, and the macromolecular structures such as lignin and cellulose are broken and reorganized to form a porous structure rich in carbon. After the constant temperature is completed, the heating is stopped, and the mixture is naturally cooled to room temperature under the continuous protection of nitrogen. The cooling rate is controlled at 3°C / min. Too fast cooling can easily cause the carbon structure to shrink and deform, affecting the development of pores, and thus obtaining biomass carbon powder;
[0057] S8. 80 g of biomass carbon powder was mixed with 350 mL of 4 mol / L potassium hydroxide solution to ensure that the biomass carbon powder was fully soaked in the potassium hydroxide solution, and the mixture was transferred to a polytetrafluoroethylene-lined autoclave, sealed and placed in an oven, heated to 700 ° C, and maintained for 100 min to allow the potassium hydroxide solution and the biomass carbon powder to react chemically at 1.5 MPa to etch the carbon skeleton and expand the pore structure;
[0058] S9. After the reaction is completed, the reactor is cooled naturally to room temperature, and the valve is slowly opened to release the pressure, and the product is transferred to an acid-resistant and alkali-resistant container, and repeatedly rinsed with a large amount of deionized water until the pH value of the washing liquid is 6.8 to remove the residual activator and reaction by-products, and then the washed carbon powder is placed in a 100°C oven and dried for 18 hours to obtain pretreated biomass carbon powder;
[0059] S10. Dissolve 60g of ferric nitrate in 1800mL of anhydrous ethanol and add 80g of a 2 / g, pore size of 2nm pretreated biomass carbon powder, ultrasonic dispersion at 280W power, 38kHz frequency for 60min, to ensure uniform impregnation of iron salt, the obtained suspension was rotary evaporated to remove ethanol, the obtained solid powder was moved to a tube furnace, nitrogen purged for 25min, flow rate of 48mL / min, heated to 830℃ at 8℃ / min, constant temperature pyrolysis for 100min, iron atoms thermal migration, anchoring, after natural cooling, pickled with 0.08mol / L hydrochloric acid for 28min, repeatedly rinsed with deionized water to neutral, vacuum dried at 78℃ for 10h, ground through a 300-mesh sieve for standby use, to obtain biochar modified metal;
[0060] S11. 675 mL of N, N-dimethylformamide and 150 mL of water were mixed to obtain a mixed solvent. 0.18 mol of ferric nitrate, 0.1 mol of ferric chloride and 0.25 mol of terephthalic acid were added to 800 mL of the mixed solvent. The mixture was dispersed evenly by ultrasonic dispersion at a power of 300 W and a frequency of 35 kHz for 40 min. The mixture was then transferred to a polytetrafluoroethylene-lined reactor and heated to 120 ° C. The mixture was stirred at 180 r / min for 30 h. After natural cooling, the suspension was centrifuged at 8000 r / min for 20 min. The precipitate was collected and washed with anhydrous ethanol and deionized water alternately for 4 times to completely remove impurities. The mixture was finally dried at 60 ° C in a vacuum environment for 16 h and ground through a 200-mesh sieve for later use. The nanoscale pores inside the mixture were crisscrossed and the iron active sites were scattered. In the scenario of solar-driven or soil in-situ electrochemical reactor, the mixture could efficiently adsorb free NO3 in irrigation water or soil. - -N, with its unique electronic structure and spatial confinement effect, catalytic reduction generates NH4 + -N, can significantly reduce the amount of exogenous nitrogen fertilizer applied, curbing NO3 from the source - -N leakage pollution risk, to obtain iron metal organic framework materials;
[0061] S12. Mixing 6 g of biochar-modified metal and 9 g of iron metal organic framework to obtain an iron metal material;
[0062] S13. Mixing 10 g of biochar, 25 g of metal-loaded modified biochar and 15 g of iron metal material to obtain a composite biochar material;
[0063] S14. 950 g of tripotassium phosphate, 75 g of potassium dihydrogen phosphate, 10 g of sodium octaborate tetrahydrate, and 1.8 g of zinc sulfate monohydrate were added to 580 g of warm water at 48 ° C. and stirred magnetically at a speed of 440 r / min for 18 min until the solid was completely dissolved to obtain a mixed solution 1;
[0064] S15. Add 50 g of composite biochar material to the mixed solution 1, stir at 180 r / min, and ultrasonically oscillate at a power of 240 W and a frequency of 28 kHz for 14 min to obtain a mixed solution, thereby obtaining a macro-element water-soluble fertilizer.
[0065] Embodiment 2: A method for preparing a macronutrient water-soluble fertilizer, comprising the following steps:
[0066] S1. Collect dry crop straw or sawdust, crush to a particle size of 2-5 mm, take 600 g and load into the carbonization furnace;
[0067] S2. The temperature was raised to 440°C at a rate of 6°C / min and pyrolyzed for 2.2 h in a nitrogen atmosphere (flow rate 22 mL / min) to fully carbonize the biomass and form a loose porous structure;
[0068] S3. After the pyrolysis is completed, the product is cooled naturally, and the product is soaked in 1% dilute hydrochloric acid for 2.2 hours to remove ash and alkaline impurities, then rinsed with deionized water until neutral, dried at 104°C, ground and passed through a 120-mesh sieve to obtain biochar;
[0069] S4. Grind the biochar into a powder of 200-240 mesh, soak 21 g of the biochar powder in 84 mL of 0.34 mol / L ferric nitrate solution, adjust the pH of the system to 10 with sodium hydroxide, soak for 9 h, dry at 84 ° C, and calcine at 520 ° C for 3 h to obtain metal-loaded modified biochar;
[0070] S5. The rice husk with a moisture content of less than 15% is crushed at a speed of 2200 rpm to ensure the consistency of particle size. If the crushing is uneven, the larger particles are prone to incomplete internal carbonization during pyrolysis. The raw material particle size is reduced to 2-5 mm, which is convenient for the subsequent pyrolysis reaction to proceed uniformly to obtain biomass raw material powder;
[0071] S6. Evenly spread the biomass raw material powder in a high-temperature resistant ceramic crucible, and control the filling amount to 55%-65% of the crucible volume to avoid excessive accumulation of materials affecting the escape of pyrolysis gas and the uniformity of heat transfer. Put the crucible filled with biomass raw material powder into the carbonization equipment, close the furnace door, and use nitrogen as a protective gas, and continuously pass it into the furnace at a flow rate of 22mL / min to replace the air in the furnace for 16min to ensure an oxygen-free environment to prevent the raw materials from oxidizing and burning in the early stage of pyrolysis. Subsequently, slowly increase the furnace temperature to 440°C at a heating rate of 6°C / min. At this stage, heating too fast can easily lead to rapid pyrolysis and gas production of biomass, resulting in material splashing and uneven carbonization;
[0072] S7. After reaching the predetermined temperature of 440°C, the constant temperature is maintained for 3 hours to allow the biomass raw material powder to be fully decomposed and transformed under the action of pyrolysis, and the macromolecular structures such as lignin and cellulose are broken and reorganized to form a porous structure rich in carbon. After the constant temperature is completed, the heating is stopped, and the mixture is naturally cooled to room temperature under the continuous protection of nitrogen. The cooling rate is controlled at 4°C / min. Too fast cooling can easily cause the carbon structure to shrink and deform, affecting the development of pores, and thus obtaining biomass carbon powder;
[0073] S8. 84 g of biomass carbon powder was mixed with 370 mL of a 4.5 mol / L potassium hydroxide solution to ensure that the biomass carbon powder was fully soaked in the potassium hydroxide solution, and the mixture was transferred to a polytetrafluoroethylene-lined autoclave, sealed, and placed in an oven, heated to 720 ° C, and maintained for 104 min to allow the potassium hydroxide solution and the biomass carbon powder to react chemically at 1.7 MPa to etch the carbon skeleton and expand the pore structure;
[0074] S9. After the reaction is completed, the reactor is cooled naturally to room temperature, and the valve is slowly opened to release the pressure, and the product is transferred to an acid-resistant and alkali-resistant container, and repeatedly rinsed with a large amount of deionized water until the pH value of the washing liquid is 6.9 to remove the residual activator and reaction by-products, and then the washed carbon powder is placed in a 104°C oven to dry for 19 hours to obtain pretreated biomass carbon powder;
[0075] S10. Dissolve 64g of ferric nitrate in 1880mL of anhydrous ethanol and add 88g of a 2 / g, pore size of 3nm pretreated biomass carbon powder, ultrasonic dispersion at 288W power, 39kHz frequency for 64min, to ensure uniform impregnation of iron salt, the obtained suspension was rotary evaporated to remove ethanol, the obtained solid powder was moved to a tube furnace, nitrogen purged for 27min, flow rate of 49mL / min, heated to 834℃ at 9℃ / min, constant temperature pyrolysis for 104min, iron atoms thermal migration, anchoring, after natural cooling, pickled with 0.09mol / L hydrochloric acid for 29min, repeatedly rinsed with deionized water to neutral, vacuum dried at 79℃ for 11h, ground through a 300-mesh sieve for standby use, to obtain biochar modified metal;
[0076] S11. 690 mL of N, N-dimethylformamide and 165 mL of water were mixed to obtain a mixed solvent. 0.19 mol of ferric nitrate, 0.11 mol of ferric chloride and 0.26 mol of 2-aminoterephthalic acid were added to 820 mL of the mixed solvent. The mixture was dispersed evenly by ultrasonic dispersion at a power of 320 W and a frequency of 37 kHz for 42 min. The mixture was then transferred to a polytetrafluoroethylene-lined reactor and heated to 124 °C. The mixture was stirred mechanically at 188 r / min for 32 h. After natural cooling, the suspension was centrifuged at 8400 r / min for 22 min. The precipitate was collected and washed alternately with anhydrous ethanol and deionized water for 5 times to completely remove impurities. The mixture was finally dried in a vacuum environment at 64 °C for 17 h and ground through a 220-mesh sieve for use. The nanoscale pores inside the mixture were crisscrossed and the iron active sites were scattered. In the scenario of solar-driven or soil in-situ electrochemical reactor, the mixture could efficiently adsorb free NO3 in irrigation water or soil. - -N, with its unique electronic structure and spatial confinement effect, catalytic reduction generates NH4 + -N, can significantly reduce the amount of exogenous nitrogen fertilizer applied, curbing NO3 from the source - -N leakage pollution risk, to obtain iron metal organic framework materials;
[0077] S12. Mixing 7 g of biochar-modified metal and 9.5 g of iron metal organic framework to obtain an iron metal material;
[0078] S13. Mixing 11 g of biochar, 26 g of metal-loaded modified biochar and 16 g of iron metal material to obtain a composite biochar material;
[0079] S14. 970 g of tripotassium phosphate, 77 g of potassium dihydrogen phosphate, 11 g of sodium octaborate tetrahydrate, and 1.9 g of zinc sulfate monohydrate were added to 588 g of warm water at 49 ° C. and magnetically stirred at a speed of 444 r / min for 19 min until the solid was completely dissolved to obtain a mixed solution 1;
[0080] S15. Add 52 g of composite biochar material to the mixed solution 1, stir at 188 r / min, and ultrasonically oscillate at a power of 244 W and a frequency of 29 kHz for 15 min to obtain a mixed solution, thereby obtaining a macro-element water-soluble fertilizer.
[0081] Embodiment 3: A method for preparing a macronutrient water-soluble fertilizer, comprising the following steps:
[0082] S1. Collect dry crop straw or sawdust, crush to a particle size of 2-5 mm, take 700 g and load into the carbonization furnace;
[0083] S2. The temperature was raised to 480°C at a rate of 7°C / min and pyrolyzed for 2.4 h in a nitrogen atmosphere (flow rate 24 mL / min) to fully carbonize the biomass and form a loose porous structure;
[0084] S3. After the pyrolysis is completed, the product is cooled naturally, and the product is soaked in 1% dilute hydrochloric acid for 2.4 hours to remove ash and alkaline impurities, then rinsed with deionized water until neutral, dried at 108°C, ground and passed through a 140-mesh sieve to obtain biochar;
[0085] S4. Grind the biochar into a powder of 200-240 mesh, soak 22 g of the biochar powder in 88 mL of 0.38 mol / L ferric nitrate solution, adjust the pH of the system to 11 with sodium hydroxide, soak for 10 h, dry at 88 ° C, and calcine at 540 ° C for 4 h to obtain metal-modified biochar;
[0086] S5. The sawdust with a moisture content of less than 15% is crushed at a speed of 2400 rpm to ensure the consistency of particle size. If the crushing is uneven, the larger particles are prone to incomplete internal carbonization during pyrolysis. The raw material particle size is reduced to 2-5 mm, which is convenient for the subsequent pyrolysis reaction to proceed uniformly to obtain biomass raw material powder;
[0087] S6. Evenly spread the biomass raw material powder in a high-temperature resistant ceramic crucible, and control the filling amount to 55%-65% of the crucible volume to avoid excessive accumulation of materials affecting the escape of pyrolysis gas and the uniformity of heat transfer. Put the crucible filled with biomass raw material powder into the carbonization equipment, close the furnace door, and use nitrogen as a protective gas, and continuously pass it into the furnace at a flow rate of 24mL / min to replace the air in the furnace for 17min to ensure an oxygen-free environment to prevent the raw materials from oxidizing and burning in the early stage of pyrolysis. Subsequently, slowly increase the furnace temperature to 480°C at a heating rate of 7°C / min. At this stage, heating too fast can easily lead to rapid pyrolysis and gas production of biomass, resulting in material splashing and uneven carbonization;
[0088] S7. After reaching the predetermined temperature of 480°C, the constant temperature is maintained for 4 hours to allow the biomass raw material powder to be fully decomposed and transformed under the action of pyrolysis, and the macromolecular structures such as lignin and cellulose are broken and reorganized to form a porous structure rich in carbon. After the constant temperature is completed, the heating is stopped, and the mixture is naturally cooled to room temperature under the continuous protection of nitrogen. The cooling rate is controlled at 5°C / min. Too fast cooling can easily cause the carbon structure to shrink and deform, affecting the development of pores, and thus obtaining biomass carbon powder;
[0089] S8. 88 g of biomass carbon powder was mixed with 390 mL of a 5 mol / L potassium hydroxide solution to ensure that the biomass carbon powder was fully soaked in the potassium hydroxide solution, and the mixture was transferred to a polytetrafluoroethylene-lined autoclave, sealed, and placed in an oven, heated to 740 ° C, and maintained for 108 min to allow the potassium hydroxide solution and the biomass carbon powder to react chemically at 1.9 MPa to etch the carbon skeleton and expand the pore structure;
[0090] S9. After the reaction is completed, the reactor is cooled naturally to room temperature, and the valve is slowly opened to release the pressure, and the product is transferred to an acid-resistant and alkali-resistant container, and repeatedly rinsed with a large amount of deionized water until the pH value of the washing liquid reaches 7.0 to remove the residual activator and reaction by-products, and then the washed carbon powder is placed in an oven at 108°C and dried for 20 hours to obtain pretreated biomass carbon powder;
[0091] S10. Dissolve 68g of ferric nitrate in 1960mL of anhydrous ethanol and add 96g of a 2 / g, pore size of 4nm pretreated biomass carbon powder, ultrasonic dispersion at 296W power, 40kHz frequency for 68min, to ensure uniform impregnation of iron salt, the obtained suspension was evaporated to remove ethanol, the obtained solid powder was moved to a tube furnace, nitrogen purged for 29min, flow rate of 50mL / min, the temperature was increased to 838℃ at 10℃ / min, constant temperature pyrolysis for 108min, iron atoms were thermally migrated and anchored, after natural cooling, pickled with 0.1mol / L hydrochloric acid for 30min, repeatedly rinsed with deionized water to neutral, vacuum dried at 80℃ for 12h, ground through a 300-mesh sieve for standby use, to obtain biochar modified metal;
[0092] S11. 705 mL of N, N-dimethylformamide and 180 mL of water were mixed to obtain a mixed solvent. 0.2 mol of ferric nitrate, 0.12 mol of ferric chloride and 0.27 mol of terephthalic acid were added to 840 mL of the mixed solvent. The mixture was dispersed evenly by ultrasonic dispersion at a power of 340 W and a frequency of 39 kHz for 44 min. The mixture was then transferred to a polytetrafluoroethylene-lined reactor and heated to 128 °C. The mixture was stirred mechanically at 196 r / min for 34 h. After natural cooling, the suspension was centrifuged at 8800 r / min for 24 min. The precipitate was collected and washed alternately with anhydrous ethanol and deionized water for 6 times to completely remove impurities. The mixture was finally dried at 68 °C in a vacuum environment for 18 h and ground through a 240-mesh sieve for use. The nanoscale pores inside the mixture were crisscrossed and the iron active sites were scattered. In the scenario of solar-driven or soil in-situ electrochemical reactor, the mixture could efficiently adsorb free NO3 in irrigation water or soil. - -N, with its unique electronic structure and spatial confinement effect, catalytic reduction generates NH4 +-N, can significantly reduce the amount of exogenous nitrogen fertilizer applied, curbing NO3 from the source - -N leakage pollution risk, to obtain iron metal organic framework materials;
[0093] S12. Mixing 8 g of biochar-modified metal and 10 g of iron metal organic framework to obtain an iron metal material;
[0094] S13. 12 g of biochar, 27 g of metal-loaded modified biochar and 17 g of iron metal material were mixed to obtain a composite biochar material;
[0095] S14. 990 g of tripotassium phosphate, 79 g of potassium dihydrogen phosphate, 12 g of sodium octaborate tetrahydrate, and 2.0 g of zinc sulfate monohydrate were added to 596 g of warm water at 50 ° C. and magnetically stirred at a speed of 448 r / min for 20 min until the solid was completely dissolved to obtain a mixed solution 1;
[0096] S15. Add 54 g of composite biochar material to the mixed solution 1, stir at 196 r / min, and ultrasonically oscillate at a power of 248 W and a frequency of 30 kHz for 16 min to obtain a mixed solution, thereby obtaining a macro-element water-soluble fertilizer.
[0097] Embodiment 4: A method for preparing a macronutrient water-soluble fertilizer, comprising the following steps:
[0098] S1. Collect dry crop straw or sawdust, crush to a particle size of 2-5 mm, take 800 g and load into the carbonization furnace;
[0099] S2. The temperature was raised to 520°C at a rate of 8°C / min and pyrolyzed for 2.6 h in a nitrogen atmosphere (flow rate 26 mL / min) to fully carbonize the biomass and form a loose porous structure;
[0100] S3. After the pyrolysis is completed, the product is cooled naturally, and the product is soaked in 1% dilute hydrochloric acid for 2.6 hours to remove ash and alkaline impurities, then rinsed with deionized water until neutral, dried at 112°C, ground and passed through a 160-mesh sieve to obtain biochar;
[0101] S4. Grind the biochar into a powder of 200-240 mesh, soak 23 g of the biochar powder in 92 mL of a 0.42 mol / L ferric nitrate solution, adjust the pH of the system to 9 with sodium hydroxide, soak for 8 h, dry at 92 ° C, and calcine at 560 ° C for 2 h to obtain a loaded metal-modified biochar;
[0102] S5. The corn stalks with a moisture content of less than 15% are crushed at a speed of 2600 rpm to ensure the consistency of particle size. If the crushing is uneven, the larger particles are prone to incomplete internal carbonization during pyrolysis. The raw material particle size is reduced to 2-5 mm, which is convenient for the subsequent pyrolysis reaction to proceed uniformly to obtain biomass raw material powder;
[0103] S6. Evenly spread the biomass raw material powder in a high-temperature resistant ceramic crucible, and control the filling amount to 55%-65% of the crucible volume to avoid excessive accumulation of materials affecting the escape of pyrolysis gas and the uniformity of heat transfer. Put the crucible filled with biomass raw material powder into the carbonization equipment, close the furnace door, and use nitrogen as a protective gas, and continuously pass it into the furnace at a flow rate of 26mL / min to replace the air in the furnace for 18min to ensure an oxygen-free environment to prevent the raw materials from oxidizing and burning in the early stage of pyrolysis. Subsequently, slowly increase the furnace temperature to 520°C at a heating rate of 6°C / min. Too fast heating at this stage can easily lead to rapid pyrolysis and gas production of biomass, resulting in material splashing and uneven carbonization;
[0104] S7. After reaching the predetermined temperature of 520°C, the constant temperature is maintained for 2 hours to allow the biomass raw material powder to be fully decomposed and transformed under the action of pyrolysis, and the macromolecular structures such as lignin and cellulose are broken and reorganized to form a porous structure rich in carbon. After the constant temperature is completed, the heating is stopped, and the mixture is naturally cooled to room temperature under the continuous protection of nitrogen. The cooling rate is controlled at 3°C / min. Too fast cooling can easily cause the carbon structure to shrink and deform, affecting the development of pores, and thus obtaining biomass carbon powder;
[0105] S8. Mix 92g of biomass carbon powder with 410mL of 4mol / L potassium hydroxide solution to ensure that the biomass carbon powder is fully soaked in the potassium hydroxide solution, transfer the mixture to a polytetrafluoroethylene-lined autoclave, seal it and put it in an oven, heat it to 760°C, and keep it for 112min to allow the potassium hydroxide solution and the biomass carbon powder to react chemically at 2.1MPa to etch the carbon skeleton and expand the pore structure;
[0106] S9. After the reaction is completed, the reactor is cooled naturally to room temperature, and the valve is slowly opened to release the pressure, and the product is transferred to an acid- and alkali-resistant container, and repeatedly rinsed with a large amount of deionized water until the pH value of the washing liquid reaches 7.1 to remove the residual activator and reaction by-products, and then the washed carbon powder is placed in an oven at 112°C and dried for 21 hours to obtain pretreated biomass carbon powder;
[0107] S10. Dissolve 72g of ferric nitrate in 2040mL of anhydrous ethanol and add 104g of a specific surface area of 720m 2 / g, pore size of 3nm pretreated biomass carbon powder, ultrasonic dispersion at 304W power, 41kHz frequency for 72min, to ensure uniform impregnation of iron salt, the obtained suspension was rotary evaporated to remove ethanol, the obtained solid powder was moved to a tube furnace, nitrogen purged for 31min, flow rate of 51mL / min, heated to 842℃ at 8℃ / min, constant temperature pyrolysis for 112min, iron atoms thermal migration, anchoring, after natural cooling, pickled with 0.11mol / L hydrochloric acid for 28min, repeatedly rinsed with deionized water to neutral, vacuum dried at 78℃ for 10h, ground through a 300-mesh sieve for standby use, to obtain biochar modified metal;
[0108] S11. 720 mL of N, N-dimethylformamide and 195 mL of water were mixed to obtain a mixed solvent. 0.21 mol of ferric nitrate, 0.1 mol of ferric chloride and 0.28 mol of 2-aminoterephthalic acid were added to 860 mL of the mixed solvent. The mixture was dispersed evenly by ultrasonic dispersion at a power of 360 W and a frequency of 41 kHz for 46 min. The mixture was then transferred to a polytetrafluoroethylene-lined reactor and heated to 132 °C. The mixture was stirred at 204 r / min for 36 h. After natural cooling, the suspension was centrifuged at 9200 r / min for 26 min. The precipitate was collected and washed with anhydrous ethanol and deionized water alternately for 4 times to completely remove impurities. The mixture was finally dried at 72 °C in a vacuum environment for 19 h and ground through a 260-mesh sieve for use. The nanoscale pores inside the mixture were crisscrossed and the iron active sites were scattered. In the scenario of solar-driven or soil in-situ electrochemical reactor, the mixture could efficiently adsorb free NO3 in irrigation water or soil. - -N, with its unique electronic structure and spatial confinement effect, catalytic reduction generates NH4 + -N, can significantly reduce the amount of exogenous nitrogen fertilizer applied, curbing NO3 from the source - -N leakage pollution risk, to obtain iron metal organic framework materials;
[0109] S12. Mixing 6 g of biochar-modified metal and 9 g of iron metal organic framework to obtain an iron metal material;
[0110] S13. 10 g of biochar, 28 g of metal-loaded modified biochar and 18 g of iron metal material were mixed to obtain a composite biochar material;
[0111] S14. 1010 g of tripotassium phosphate, 81 g of potassium dihydrogen phosphate, 10 g of sodium octaborate tetrahydrate, and 2.1 g of zinc sulfate monohydrate were added to 604 g of warm water at 51 ° C. and magnetically stirred at a speed of 452 r / min for 21 min until the solid was completely dissolved to obtain a mixed solution 1;
[0112] S15. Add 56 g of composite biochar material to the mixed solution 1, stir at 204 r / min, and ultrasonically oscillate at a power of 252 W and a frequency of 31 kHz for 14 min to obtain a mixed solution, thereby obtaining a macro-element water-soluble fertilizer.
[0113] Embodiment 5: A method for preparing a macronutrient water-soluble fertilizer, comprising the following steps:
[0114] S1. Collect dry crop straw or sawdust, crush to a particle size of 2-5 mm, take 900 g and load into the carbonization furnace;
[0115] S2. The temperature was raised to 560°C at a rate of 9°C / min and pyrolyzed for 2.8 h in a nitrogen atmosphere (flow rate 28 mL / min) to fully carbonize the biomass and form a loose porous structure;
[0116] S3. After the pyrolysis is completed, the product is cooled naturally, and the product is soaked in 1% dilute hydrochloric acid for 2.8 hours to remove ash and alkaline impurities, then rinsed with deionized water until neutral, dried at 116°C, ground and passed through a 180-mesh sieve to obtain biochar;
[0117] S4. Grind the biochar into a powder of 200-240 mesh, soak 24 g of the biochar powder in 96 mL of a 0.46 mol / L ferric nitrate solution, adjust the pH of the system to 10 with sodium hydroxide, soak for 9 h, dry at 96 ° C, and calcine at 580 ° C for 3 h to obtain a loaded metal modified biochar;
[0118] S5. The rice husk with a moisture content of less than 15% is crushed at a speed of 2800 rpm to ensure the consistency of particle size. If the crushing is uneven, the larger particles are prone to incomplete internal carbonization during pyrolysis. The raw material particle size is reduced to 2-5 mm, which is convenient for the subsequent pyrolysis reaction to proceed uniformly to obtain biomass raw material powder;
[0119] S6. Evenly spread the biomass raw material powder in a high-temperature resistant ceramic crucible, and control the filling amount to 55%-65% of the crucible volume to avoid excessive accumulation of materials affecting the escape of pyrolysis gas and the uniformity of heat transfer. Put the crucible filled with biomass raw material powder into the carbonization equipment, close the furnace door, and use nitrogen as a protective gas, and continuously pass it into the furnace at a flow rate of 28mL / min to replace the air in the furnace for 19min to ensure an oxygen-free environment to prevent the raw materials from oxidizing and burning in the early stage of pyrolysis. Subsequently, slowly increase the furnace temperature to 560°C at a heating rate of 7°C / min. Too fast heating at this stage can easily lead to rapid pyrolysis and gas production of biomass, resulting in material splashing and uneven carbonization;
[0120] S7. After reaching the predetermined temperature of 560°C, the constant temperature is maintained for 3 hours to allow the biomass raw material powder to be fully decomposed and transformed under the action of pyrolysis, and the macromolecular structures such as lignin and cellulose are broken and reorganized to form a porous structure rich in carbon. After the constant temperature is completed, the heating is stopped, and the mixture is naturally cooled to room temperature under the continuous protection of nitrogen. The cooling rate is controlled at 4°C / min. Too fast cooling can easily cause the carbon structure to shrink and deform, affecting the development of pores, and thus obtaining biomass carbon powder;
[0121] S8. Mix 96g of biomass carbon powder with 430mL of 4.5mol / L potassium hydroxide solution to ensure that the biomass carbon powder is fully immersed in the potassium hydroxide solution, transfer the mixture to a polytetrafluoroethylene-lined high-pressure reactor, seal it and put it into an oven, heat it to 780°C, and keep it for 116min to allow the potassium hydroxide solution and the biomass carbon powder to react chemically at 2.3MPa to etch the carbon skeleton and expand the pore structure;
[0122] S9. After the reaction is completed, after the reactor is naturally cooled to room temperature, slowly open the valve to release the pressure, transfer the product to an acid- and alkali-resistant container, and repeatedly rinse with a large amount of deionized water until the pH value of the washing liquid reaches 6.9 to remove the residual activator and reaction by-products. Then, the washed carbon powder is placed in an oven at 116°C and dried for 19 hours to obtain pretreated biomass carbon powder;
[0123] S10. Dissolve 76g of ferric nitrate in 2120mL of anhydrous ethanol and add 112g of a specific surface area of 760m 2 / g, pore size of 4nm pretreated biomass carbon powder, ultrasonic dispersion at 312W power, 41kHz frequency for 76min, to ensure uniform impregnation of iron salt, the obtained suspension was rotary evaporated to remove ethanol, the obtained solid powder was moved to a tube furnace, nitrogen purged for 33min, flow rate of 50mL / min, the temperature was increased to 846℃ at 9℃ / min, constant temperature pyrolysis for 116min, iron atoms were thermally migrated and anchored, after natural cooling, pickled with 0.1mol / L hydrochloric acid for 29min, repeatedly rinsed with deionized water to neutral, vacuum dried at 79℃ for 11h, ground through a 300-mesh sieve for standby use, to obtain biochar modified metal;
[0124] S11. 735 mL of N, N-dimethylformamide and 210 mL of water were mixed to obtain a mixed solvent. 0.19 mol of ferric nitrate, 0.11 mol of ferric chloride and 0.29 mol of terephthalic acid were added to 880 mL of the mixed solvent. The mixture was dispersed evenly by ultrasonic dispersion at a power of 380 W and a frequency of 43 kHz for 48 min. The mixture was then transferred to a polytetrafluoroethylene-lined reactor and heated to 136 ° C. The mixture was stirred at 212 r / min for 38 h. After natural cooling, the suspension was centrifuged at 9600 r / min for 28 min. The precipitate was collected and washed with anhydrous ethanol and deionized water alternately for 5 times to completely remove impurities. The mixture was finally dried at 76 ° C in a vacuum environment for 18 h. The mixture was ground and passed through a 280-mesh sieve for use. The nanoscale pores inside the mixture were crisscrossed and the iron active sites were scattered. In the scenario of solar-driven or soil in-situ electrochemical reactor, the mixture could efficiently adsorb free NO3 in irrigation water or soil. - -N, with its unique electronic structure and spatial confinement effect, catalytic reduction generates NH4 + -N, can significantly reduce the amount of exogenous nitrogen fertilizer applied, curbing NO3 from the source - -N leakage pollution risk, to obtain iron metal organic framework materials;
[0125] S12. Mixing 7 g of biochar-modified metal and 9.5 g of iron metal organic framework to obtain an iron metal material;
[0126] S13. 11 g of biochar, 29 g of metal-loaded modified biochar and 17 g of iron metal material were mixed to obtain a composite biochar material;
[0127] S14. 1030 g of tripotassium phosphate, 83 g of potassium dihydrogen phosphate, 11 g of sodium octaborate tetrahydrate, and 1.9 g of zinc sulfate monohydrate were added to 612 g of warm water at 50 ° C. and magnetically stirred at a speed of 452 r / min for 19 min until the solid was completely dissolved to obtain a mixed solution 1;
[0128] S15. Add 58 g of composite biochar material to the mixed solution 1, stir at 212 r / min, and ultrasonically oscillate at a power of 256 W and a frequency of 30 kHz for 15 min to obtain a mixed solution, thereby obtaining a macro-element water-soluble fertilizer.
[0129] Embodiment 6: A method for preparing a macronutrient water-soluble fertilizer, comprising the following steps:
[0130] S1. Collect dry crop straw or sawdust, crush to a particle size of 2-5 mm, take 1000 g and load it into the carbonization furnace;
[0131] S2. The temperature was raised to 600 °C at a rate of 10 °C / min and pyrolyzed for 3 h in a nitrogen atmosphere (flow rate 30 mL / min) to fully carbonize the biomass and form a loose porous structure;
[0132] S3. After the pyrolysis is completed, the product is cooled naturally, and the product is soaked in 1% dilute hydrochloric acid for 3 hours to remove ash and alkaline impurities, then rinsed with deionized water until neutral, dried at 120°C, ground and passed through a 200-mesh sieve to obtain biochar;
[0133] S4. Grind the biochar into a powder of 200-240 mesh, soak 25 g of the biochar powder in 100 mL of 0.5 mol / L ferric nitrate solution, adjust the pH of the system to 11 with sodium hydroxide, soak for 10 h, dry at 100 ° C, and calcine at 600 ° C for 4 h to obtain metal-modified biochar;
[0134] S5. The sawdust with a moisture content of less than 15% is crushed at a speed of 3000 rpm to ensure the consistency of particle size. If the crushing is uneven, the larger particles are prone to incomplete internal carbonization during pyrolysis. The raw material particle size is reduced to 2-5 mm, which is convenient for the subsequent pyrolysis reaction to proceed uniformly to obtain biomass raw material powder;
[0135] S6. Evenly spread the biomass raw material powder in a high-temperature resistant ceramic crucible, and control the filling amount to 55%-65% of the crucible volume to avoid excessive accumulation of materials affecting the escape of pyrolysis gas and the uniformity of heat transfer. Put the crucible filled with biomass raw material powder into the carbonization equipment, close the furnace door, and use nitrogen as a protective gas, and continuously pass it into the furnace at a flow rate of 30mL / min to replace the air in the furnace for 20min to ensure an oxygen-free environment to prevent the raw materials from oxidizing and burning in the early stage of pyrolysis. Subsequently, slowly increase the furnace temperature to 600°C at a heating rate of 8°C / min. At this stage, heating too fast can easily lead to rapid pyrolysis and gas production of biomass, resulting in material splashing and uneven carbonization;
[0136] S7. After reaching the predetermined temperature of 600°C, the constant temperature is maintained for 4 hours to allow the biomass raw material powder to be fully decomposed and transformed under the action of pyrolysis, and the macromolecular structures such as lignin and cellulose are broken and reorganized to form a porous structure rich in carbon. After the constant temperature is completed, the heating is stopped, and the mixture is naturally cooled to room temperature under the continuous protection of nitrogen. The cooling rate is controlled at 5°C / min. Too fast cooling can easily cause the carbon structure to shrink and deform, affecting the development of pores, and thus obtaining biomass carbon powder;
[0137] S8. Mix 100 g of biomass carbon powder with 450 mL of 5 mol / L potassium hydroxide solution to ensure that the biomass carbon powder is fully immersed in the potassium hydroxide solution, transfer the mixture to a polytetrafluoroethylene-lined autoclave, seal it and place it in an oven, heat it to 800 ° C, and keep it for 120 min to allow the potassium hydroxide solution and the biomass carbon powder to react chemically at 2.5 MPa to etch the carbon skeleton and expand the pore structure;
[0138] S9. After the reaction is completed, the reactor is cooled to room temperature naturally, and the valve is slowly opened to release the pressure, and the product is transferred to an acid- and alkali-resistant container, and repeatedly rinsed with a large amount of deionized water until the pH value of the washing liquid reaches 7.2 to remove the residual activator and reaction by-products, and then the washed carbon powder is placed in an oven at 120°C and dried for 22 hours to obtain pretreated biomass carbon powder;
[0139] S10. Dissolve 80g of ferric nitrate in 2200mL of anhydrous ethanol and add 120g of a 2 / g, pore size of 5nm pretreated biomass carbon powder, ultrasonic dispersion at 320W power, 42kHz frequency for 80min, to ensure uniform impregnation of iron salt, the obtained suspension was rotary evaporated to remove ethanol, the obtained solid powder was moved to a tube furnace, nitrogen purged for 35min, flow rate of 52mL / min, heated to 850℃ at 10℃ / min, constant temperature pyrolysis for 120min, iron atoms thermal migration, anchoring, after natural cooling, pickled with 0.12mol / L hydrochloric acid for 30min, repeatedly rinsed with deionized water to neutral, vacuum dried at 80℃ for 12h, ground through a 300-mesh sieve for standby use, to obtain biochar modified metal;
[0140] S11. 750 mL of N, N-dimethylformamide and 225 mL of water were mixed to obtain a mixed solvent. 0.22 mol of ferric nitrate, 0.12 mol of ferric chloride and 0.3 mol of 2-aminoterephthalic acid were added to 900 mL of the mixed solvent. The mixture was dispersed evenly by ultrasonic dispersion at a power of 400 W and a frequency of 45 kHz for 50 min. The mixture was then transferred to a polytetrafluoroethylene-lined reactor and heated to 140 ° C. The mixture was stirred at 220 r / min for 40 h. After natural cooling, the suspension was centrifuged at 10000 r / min for 30 min. The precipitate was collected and washed with anhydrous ethanol and deionized water alternately for 6 times to completely remove impurities. The mixture was finally dried at 80 ° C in a vacuum environment for 20 h. The mixture was ground through a 300-mesh sieve for use. The nanoscale pores inside the mixture were crisscrossed and the iron active sites were scattered. In the scenario of solar-driven or soil in-situ electrochemical reactor, the mixture could efficiently adsorb free NO3 in irrigation water or soil. - -N, with its unique electronic structure and spatial confinement effect, catalytic reduction generates NH4 + -N, can significantly reduce the amount of exogenous nitrogen fertilizer applied, curbing NO3 from the source - -N leakage pollution risk, to obtain iron metal organic framework materials;
[0141] S12. Mixing 8 g of biochar-modified metal and 10 g of iron metal organic framework to obtain an iron metal material;
[0142] S13. Mixing 12 g of biochar, 30 g of metal-loaded modified biochar and 18 g of iron metal material to obtain a composite biochar material;
[0143] S14. 1050 g of tripotassium phosphate, 85 g of potassium dihydrogen phosphate, 12 g of sodium octaborate tetrahydrate, and 2.2 g of zinc sulfate monohydrate were added to 620 g of warm water at 52 ° C. and stirred magnetically at a speed of 460 r / min for 22 min until the solid was completely dissolved to obtain a mixed solution 1;
[0144] S15. Add 60 g of composite biochar material to the mixed solution 1, stir at 220 r / min, and ultrasonically oscillate at a power of 260 W and a frequency of 32 kHz for 16 min to obtain a mixed solution, thereby obtaining a macro-element water-soluble fertilizer.
[0145] Comparative Example 1:
[0146] Compared with Example 1, this comparative example does not add "composite biochar material" during the preparation process of "macro-element water-soluble fertilizer", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a macro-element water-soluble fertilizer is obtained.
[0147] Comparative Example 2:
[0148] Compared with Example 1, this comparative example does not add "metal-loaded modified biochar" during the preparation of the "macro-element water-soluble fertilizer", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a macro-element water-soluble fertilizer is obtained.
[0149] Comparative Example 3:
[0150] Compared with Example 1, this comparative example does not add "biochar modified metal" during the preparation of the "macro-element water-soluble fertilizer", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a macro-element water-soluble fertilizer is obtained.
[0151] Comparative Example 4:
[0152] Compared with Example 1, this comparative example only adjusts the amount of "biochar" in the "composite biochar material" from "10g" to "25g", and adjusts the amount of "loaded metal modified biochar" in the "composite biochar material" from "25g" to "10g", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a large amount of element water-soluble fertilizer is obtained.
[0153] Performance test: The following performance tests were performed on the macronutrient water-soluble fertilizers prepared in Examples 1 to 6 and Comparative Examples 1 to 4:
[0154] Nitrogen adsorption and conversion performance test
[0155] Determination of nitrate nitrogen adsorption: accurately weigh 0.5g of fertilizer sample and place it in a conical flask containing 100mL of 50mg / L nitrate nitrogen solution; oscillate on a constant temperature oscillator at 25℃ and 150r / min for 24h to allow the sample to fully contact with the solution and reach adsorption equilibrium; after the oscillation, filter the solution through a 0.45μm filter membrane and use an ion chromatograph to determine the residual concentration of nitrate nitrogen in the filtrate. According to the difference in nitrate nitrogen concentration before and after adsorption, the nitrate nitrogen adsorption is calculated using the following formula, recorded as Q, in mg / g:
[0156]
[0157] Where Q is the adsorption amount, C0 is the initial concentration, C e is the equilibrium concentration, V is the volume of the solution, and m is the mass of the sample;
[0158] Determination of ammonium nitrogen production: After the nitrate nitrogen adsorption experiment, the samples and solution system are transferred to a sealed light-proof container to simulate the solar-driven or soil in-situ electrochemical reactor scenario, and the reaction is continued for 48 hours at a light intensity of 5000-8000 lux and a temperature of 25-30°C; after the reaction, the solution is filtered again, and the amount of ammonium nitrogen produced in the filtrate is determined by a flow analyzer or indigo blue colorimetry to evaluate the catalytic reduction ability of the fertilizer on nitrate nitrogen, which is recorded as S in mg / g;
[0159] Soil improvement performance test
[0160] Soil bulk density determination: In the field test area, the fertilizers prepared in Examples 1-6 and Comparative Examples 1-4 were applied, and the same crops were planted. During the flowering period of the crops, the original soil samples were taken in each area by the ring knife method, and the soil samples in the ring knife were brought back to the laboratory. The excess soil at both ends of the ring knife was removed, and the total mass of the ring knife and the soil sample was weighed. The wet weight of the soil sample was obtained by subtracting the mass of the ring knife. The moisture content of the soil sample was then determined by the drying method. Combined with the volume of the ring knife, the soil bulk density was calculated using the following formula, recorded as ρ, in units of g / cm 3 :
[0161]
[0162] Where ρ is the bulk density, m is the dry soil mass, V is the ring cutter volume, and w is the water content;
[0163] Soil porosity calculation: According to the soil bulk density measurement results, the soil porosity is calculated using the following formula, recorded as P, in %:
[0164]
[0165] Where P is the porosity, ρ is the measured bulk density, s is the soil particle density, generally taken as 2.65g / cm3 ;
[0166] Soil enzyme activity assay:
[0167] In the fertilizer treatment area, soil samples from the soil surface layer of 0-20 cm were collected, mixed evenly and passed through a 2 mm sieve, and the soil urease activity was determined by colorimetry: 5 g of fresh soil was weighed and placed in a stoppered conical flask, 10 mL of 1% urea and 0.05 mol / L phosphate buffer (pH = 7.0) was added, and the mixture was cultured at 37°C for 24 h. After filtration, the filtrate was taken, a color developer was added, and colorimetry was performed at a wavelength of 578 nm. The urease activity (the enzyme activity per gram of soil sample within 24 h was expressed as milligrams of ammonia nitrogen) was calculated according to the standard curve, which was recorded as M, and the unit was mg / g·24h;
[0168] Phosphatase activity determination: Similarly weigh 5g of fresh soil, add 20mL 0.05mol / L disodium p-nitrophenylphosphate solution (p=6.5) and 0.5g toluene, shake at 37℃ for 1h, filter and take the filtrate, compare the color at a wavelength of 400nm, calculate the phosphatase activity according to the standard curve (expressed as milligrams of p-nitrophenol per gram of soil sample within 1h), compare the differences in soil enzyme activity under different fertilizer treatments, and reflect the soil fertility conversion capacity, recorded as N, the unit is mg / g·1h;
[0169] Crop growth and quality index testing:
[0170] Crop biomass determination: At the crop harvest period, 5 representative plants were randomly selected from each fertilizer treatment area, the aboveground and underground parts were separated, the soil around the roots was cleaned, the surface moisture was dried with absorbent paper, and the aboveground fresh weight and underground fresh weight were weighed respectively; then they were placed in an oven at 105°C for 30 min, and then adjusted to 80°C to dry to constant weight, and the aboveground dry weight was weighed, recorded as T, in g / plant, and the effects of different fertilizer treatments on crop biomass accumulation were statistically analyzed;
[0171] Crop yield statistics: Conduct actual yield measurement in the fertilizer treatment area, record the total weight of crop grains or fruits harvested in each plot, convert it into yield per unit area (kg / mu), recorded as Y, in kg / mu, and compare the yield data to evaluate the yield-increasing effect of the fertilizer.
[0172] Fruit quality analysis: for vegetables and fruit crops, the fruit quality indicators are measured. For example, the soluble sugar content of the fruit is measured by the anthrone colorimetric method. A certain amount of fruit homogenate is taken, ethanol is added for extraction, and then centrifuged and diluted to react with anthrone reagent. The color is measured at a wavelength of 620nm, and the soluble sugar content is calculated according to the standard curve, which is recorded as L and the unit is %;
[0173] Determination of vitamin C content: 2,6-dichloroindophenol titration method was used, the titrant was calibrated with standard ascorbic acid solution, the fruit homogenate filtrate was titrated, and the vitamin C content was calculated based on the volume of the consumed titrant, recorded as V, in mg / 100g;
[0174] Determination of protein content (for cereal grains): Use the Kjeldahl method to grind the grains, digest, distill, and titrate them. Calculate the nitrogen content and then multiply it by the protein conversion factor (generally 5.95 for cereals) to get the protein content, recorded as U, in %, to comprehensively evaluate the effect of fertilizers on improving crop quality;
[0175] The results are shown in Table 1 below:
[0176] Table 1
[0177] project Q S ρ P M N T Y L V U Example 1 12.5 9.2 1.22 53 2.8 1.6 185 580 12.8 35 10.5 Example 2 13.2 9.8 1.20 55 3.0 1.7 190 600 13.2 37 10.8 Example 3 14.0 10.5 1.18 56 3.2 1.8 198 620 13.6 38 11.0 Example 4 12.8 9.4 1.21 54 2.9 1.6 188 590 12.9 36 10.6 Example 5 13.6 10.0 1.19 55 3.1 1.7 192 610 13.3 37 10.9 Example 6 14.5 10.8 1.17 57 3.3 1.9 200 630 13.8 39 11.2 Comparative Example 1 3.5 0.5 1.36 40 1.0 0.6 120 380 10.5 28 9.0 Comparative Example 2 8.0 4.5 1.28 46 1.8 1.1 150 480 11.5 32 9.8 Comparative Example 3 7.5 4.0 1.29 45 1.7 1.0 145 460 11.2 31 9.6 Comparative Example 4 10.5 6.8 1.25 49 2.2 1.3 165 520 12.0 33 10.2
[0178] Data Analysis:
[0179] As can be seen from Table 1, in Examples 1-6, the composite biochar material performs excellently. The porous structure of the biochar itself provides physical adsorption sites, and its surface functional groups such as carboxyl and phenolic hydroxyl groups can adsorb nitrate nitrogen through electrostatic attraction. In addition, the biochar preparation conditions in the examples are optimized, and high-temperature pyrolysis (400-600°C) forms abundant micropores (<2nm) and mesopores (2-50nm), and the specific surface area reaches a certain range (such as the specific surface area of the biomass carbon powder after pretreatment in some examples is 500-800m 2 / g), enhancing the nitrate nitrogen capture capacity, so the nitrate nitrogen adsorption amount is considerable, mostly 12-14mg / g. -The loaded metal modified biochar is upgraded on this basis. Iron nitrate impregnation pyrolysis introduces iron active sites, improves the specificity of chemical adsorption of nitrate nitrogen, and the iron sites promote electron transfer, which is beneficial to the subsequent reduction reaction; at the same time, the biochar skeleton support prevents iron agglomeration, ensures activity, and synergistically enhances the continuity of adsorption and catalysis. The amount of ammonium nitrogen generated accounts for 73%-75% of the adsorbed nitrate nitrogen. -The iron metal organic framework material contains nanopores (0.5-2nm) that precisely confine nitrate nitrogen. The unique electronic structure (3d orbital characteristics) of the iron active site reduces the energy barrier of the nitrate nitrogen reduction reaction, guides the orderly rupture of the NO bond and hydrogenation into ammonium nitrogen, and the multi-step catalysis is efficient and precise, which complements biochar materials, improves the nitrogen conversion cycle, reduces nitrogen loss, ensures the nitrogen source supply of crops and reduces the risk of environmental pollution. In contrast, in Example 1, no composite biochar material was added, and the physical and chemical adsorption "primary screening" function of biochar and modified materials was missing. A large amount of nitrate nitrogen was free and not intercepted, and the adsorption amount was only 3.5 mg / g. There was a lack of substrate for subsequent conversion, and very little ammonium nitrogen was generated. In contrast, in Example 2, no metal-modified biochar was loaded. Although the basic adsorption of biochar existed, it lacked iron activity enhancement, and the adsorption capacity was limited (8 mg / g). In addition, due to the lack of efficient catalysis of modified iron sites, the ammonium nitrogen generation rate was as low as 56.3%, indicating that metal modification has a key influence on the rate and degree of nitrogen conversion, affecting the conversion of nitrogen from adsorbed state to available nitrogen for crops. The conversion efficiency of nitrate nitrogen was improved; in comparative example 3, the biochar-modified metal was missing. Although the iron-metal organic framework material had the conversion ability, it lacked the auxiliary stable structure and synergistic adsorption territorial effect of the biochar-modified metal. The continuity of nitrate nitrogen adsorption conversion decreased, and the overall performance decreased; in comparative example 4, the ratio of biochar to loaded metal-modified biochar was adjusted to destroy the original balance. The excessive biochar caused the iron active sites to be relatively dispersed, and the loaded metal-modified biochar was reduced, weakening its dominant adsorption and catalytic efficiency. The adsorption amount dropped to 10.5 mg / g, and the ammonium nitrogen generation ratio was 64.8%, which deviated from the ideal state.
[0180] In Examples 1-6 of the present invention, the biochar is pyrolyzed to generate a loose porous carbon structure to fill the gaps between soil particles. For example, at 400-600°C, under a specific temperature rise and pyrolysis time control, stable pores are formed, the cohesion of soil particles is reduced, and the soil bulk density is increased from 1.38 g / cm 3 Around 1.17-1.22g / cm 3 The porosity is increased to 53%-57%. The macropores help ventilation and drainage, and the micropores retain water and fertilizer. The three-phase distribution is optimized, providing a channel for crop root extension and microbial shuttle. At the chemical level, the biochar functional groups buffer the soil acid and alkali, stabilize the pH, and adsorb and exchange Ca 2+ Mg 2+The metal-modified biochar and biochar-modified metals introduce elements such as iron, which affect the soil chemical microenvironment through dissolution, precipitation, ion exchange, etc., activate urease, phosphatase, etc. In the embodiment, the urease activity is 2.8-3.3 mg / g·24h (phosphatase activity is 1.6-1.9 mg / g·1h), accelerate the conversion of organic nitrogen and phosphorus, form an "internal cycle" of soil fertility, nourish crop growth, and increase the abundance of microorganisms due to the favorable habitat and sufficient food (carbon source, nutrients). Metabolites improve soil aggregates. , enhance the stability of soil structure and achieve positive feedback of soil ecology; while comparative example 1 has no composite biochar, the soil structure improvement lacks a "foundation", the bulk density is high, the porosity is low, and the microbial activity is weak, which is due to the lack of physical support and chemical interaction of biochar; comparative examples 2 and 3 have less metal-modified biochar and biochar-modified metal loading respectively, the soil chemical improvement lacks a "catalyst", nutrient activation and enzymatic reaction are slow, microbial reproduction is restricted, and a complete soil improvement "power chain" cannot be constructed; comparative example 4 has an unbalanced proportion, and some functions are weakened, which affects the rooting of crops and the foundation of nutrient uptake.
[0181] The fertilizers in Examples 1-6 of the present invention are supplied with ammonium nitrogen by the iron metal organic framework material and the composite biochar in relay according to the nitrogen demand rhythm of the crop, which matches the absorption preference of the crop. For example, cereal crops such as rice obtain a stable nitrogen source in each growth period, the root system has sufficient absorption power, the stems and leaves grow vigorously, and the above-ground dry weight increases by 20%-30% compared with the control, which provides energy for the accumulation and transportation of photosynthetic products, laying a foundation for high yield. The underground root system grows and stretches due to the excellent soil porosity and active nutrients, and the absorption area is expanded, and the biomass increases synchronously, supporting the growth of the above-ground part, improving the soil structure and reducing the root resistance by 30%-40%, the root system can absorb water and fertilizer smoothly, the enzyme-active soil "processing plant" efficiently supplies nutrients, the microbial "symbiotic partner" inhibits diseases and promotes hormone secretion, the crop has strong stress resistance, stable growth, excellent fruit development, and rising quality indicators, such as soluble sugar in vegetables is increased by 10%-20%, vitamin C in fruits is increased by 8%-15%, and cereal protein is increased by 8%-12%, which is due to the improvement of comprehensive fertility and the reduction of stress, so as to achieve high-quality and high-yield double harvests. However, the lack of composite biochar in comparison example 1 resulted in nitrogen disorder and poor soil, making the crops "hungry and crowded", and their growth was limited by nutrient deficiency, with a yield drop of 27% (440kg / mu for the control and 380kg / mu for the comparison), and the quality declined due to nutrient imbalance and soil stress; the ingredients of comparison examples 2 and 3 were incomplete, and nitrogen conversion or soil improvement was limited, resulting in "malnutrition" or "unsuitable environment" for crop growth, and the yield hovered at a low level, and the quality was difficult to meet the standards; the unbalanced ratio of comparison example 4 disrupted the synergy, the crop growth microenvironment fluctuated, the nutrient supply fluctuated, and the yield was about 20% away from the ideal.
[0182] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0183] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A macro-element water-soluble fertilizer, characterized in that: The method is prepared from the following raw materials in parts by weight: 950-1050 parts of tripotassium phosphate, 75-85 parts of potassium dihydrogen phosphate, 10-12 parts of sodium octaborate tetrahydrate, 1.8-2.2 parts of zinc sulfate monohydrate, 580-620 parts of water, and 50-60 parts of composite biochar material; The composite biochar material is prepared from biochar, metal-loaded modified biochar and iron metal material; The metal-loaded modified biochar is biochar loaded with iron elements.
2. The macronutrient water-soluble fertilizer according to claim 1, characterized in that: The mass ratio of biochar, metal-loaded modified biochar and iron metal material in the composite biochar material is 10-12:25-30:15-18.
3. The macro-element water-soluble fertilizer according to claim 2, characterized in that: The preparation process of the biochar is as follows: Step A1. Collect dry crop straw or sawdust, crush to a particle size of 2-5 mm, and take 500-1000 g into the carbonization furnace; Step A2. Raise the temperature to 400-600°C at a rate of 5-10°C / min, and pyrolyze in a nitrogen atmosphere at a flow rate of 20-30 mL / min for 2-3 h; Step A3. After the pyrolysis is completed, the product is cooled naturally, and the product is soaked in 1% dilute hydrochloric acid for 2-3 hours, then rinsed with deionized water until neutral, dried at 100-120°C, ground, and passed through a 100-200 mesh sieve to obtain biochar.
4. The macro-element water-soluble fertilizer according to claim 2, characterized in that: The preparation process of the metal-loaded modified biochar is as follows: Grind the biochar into a powder of 200-240 mesh, soak the biochar powder in a ferric nitrate solution, adjust the pH of the system to 9-11 with sodium hydroxide, soak for 8-10 hours, dry at 80-100° C., and calcine at 500-600° C. for 2-4 hours to obtain a loaded metal modified biochar; The dosage ratio of the biochar to the ferric nitrate solution is 2-2.5 g: 8-10 mL, and the concentration of the ferric nitrate solution is 0.3-0.5 mol / L.
5. The macro-element water-soluble fertilizer according to claim 2, characterized in that: The iron metal materials include biochar modified metals and iron metal organic framework materials; The mass ratio of the biochar modified metal to the iron metal organic framework in the iron metal material is 6-8:9-10; The preparation process of the biochar-modified metal is as follows: Step B1. The biomass raw material is crushed at a rotation speed of 2000-3000 rpm to reduce the raw material particle size to 2-5 mm to obtain biomass raw material powder; Step B2. Evenly spread the biomass raw material powder in a high-temperature resistant ceramic crucible, and control the filling amount to 55%-65% of the crucible volume. Place the crucible filled with the biomass raw material powder into the carbonization equipment, close the furnace door, and use nitrogen as a protective gas. Continue to pass it into the furnace at a flow rate of 20-30mL / min to replace the air in the furnace for 15-20min, and slowly increase the furnace temperature to 400-600℃ at a heating rate of 5-8℃ / min; Step B3. After reaching a predetermined temperature of 400-600°C, maintain a constant temperature state for 2-4 hours, stop heating, and naturally cool to room temperature under continuous nitrogen protection, with the cooling rate controlled at 3-5°C / min to obtain biomass carbon powder; Step B4. Mix the biomass carbon powder and potassium hydroxide solution evenly, transfer the mixture to a polytetrafluoroethylene-lined autoclave, seal it and place it in an oven, raise the temperature to 700-800°C, maintain it for 100-120 minutes, and the pressure is 1.5-2.5MPa; Step B5. After the reaction is completed, the reactor is cooled naturally to room temperature, and the product is transferred to an acid- and alkali-resistant container, and washed with a large amount of deionized water until the pH value of the washing liquid is 6.8-7.
2. The washed carbon powder is then placed in an oven at 100-120°C and dried for 18-22 hours to obtain pretreated biomass carbon powder; Step B6. Dissolve ferric nitrate in anhydrous ethanol, add pretreated biomass carbon powder, and ultrasonically disperse for 60-80 minutes at a power of 280-320 W and a frequency of 38-42 kHz. The obtained suspension is evaporated to remove ethanol, and the obtained solid powder is transferred to a tubular furnace, purged with nitrogen for 25-35 minutes at a flow rate of 48-52 mL / min, and heated to 830-850°C at a rate of 8-10°C / min. Constant temperature pyrolysis is performed for 100-120 minutes. After the reaction is completed, it is naturally cooled, pickled with hydrochloric acid at a concentration of 0.08-0.12 mol / L for 28-30 minutes, repeatedly rinsed with deionized water until neutral, vacuum dried at 78-80°C for 10-12 hours, ground through a 300 mesh sieve for use, and biochar modified metals are obtained.
6. The macro-element water-soluble fertilizer according to claim 5, characterized in that: The biomass raw material in step B1 is any one of corn stalks, rice husks and sawdust; The moisture content of the biomass raw material in step B1 is less than 15%; The ratio of the biomass carbon powder to potassium hydroxide in step B4 is 8-10 g: 35-45 mL; The concentration of the potassium hydroxide solution in step B4 is 4-5 mol / L.
7. The macro-element water-soluble fertilizer according to claim 5, characterized in that: The usage ratio of ferric nitrate, anhydrous ethanol and pretreated biomass carbon powder in step B6 is 6-8 g: 180-220 mL: 8-12 g; The specific surface area of the pretreated biomass carbon powder in step B6 is 600-800m 2 / g, the pore size of pretreated biomass carbon powder is 2-5nm.
8. The macro-element water-soluble fertilizer according to claim 5, characterized in that: The preparation process of the iron metal organic framework material is as follows: Ferric nitrate, ferric chloride and an organic ligand are added to a mixed solvent, dispersed by ultrasound, and transferred to a polytetrafluoroethylene-lined reactor. The temperature is raised to 120-140°C, and the reaction is continued for 30-40 hours under mechanical stirring at 180-220 r / min. After natural cooling, the suspension is subjected to high-speed centrifugation at 8000-10000 r / min for 20-30 minutes, and the precipitate is collected and alternately rinsed with anhydrous ethanol and deionized water for 4-6 times, and finally dried in a vacuum environment at 60-80°C for 16-20 hours, and ground through a 200-300 mesh sieve to obtain an iron metal organic framework material.
9. The macro-element water-soluble fertilizer according to claim 8, characterized in that: The dosage ratio of the ferric nitrate, ferric chloride, organic ligand and mixed solvent is 0.18-0.22 mol: 0.1-0.12 mol: 0.25-0.3 mol: 800-900 mL; The organic ligand is any one of terephthalic acid and 2-aminoterephthalic acid; The mixed solvent is obtained by mixing N,N-dimethylformamide and water in a volume ratio of 675-750:150-225; The ultrasonic dispersion has a power of 300-400 W, a frequency of 35-45 kHz, and a time of 40-50 min.
10. The method for preparing the water-soluble fertilizer of a large amount of elements according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1. Potassium phosphate tripotassium dihydrogen phosphate sodium octaborate tetrahydrate and zinc sulfate monohydrate are placed in 48-52° C. warm water, and magnetically stirred at a speed of 440-460 r / min for 18-22 min until the solid is completely dissolved to obtain a mixed solution 1; Step S2. Add the composite biochar material to the mixed solution 1, stir at 180-220 r / min, and ultrasonically oscillate at a power of 240-260 W and a frequency of 28-32 kHz for 14-16 min to obtain a mixed solution, thereby obtaining a macro-element water-soluble fertilizer.
Citation Information
Patent Citations
Preparation and application methods of modified porous magnetic metal organic framework composite biochar
CN117718017A
Biomass carbon water-soluble fertilizer for promoting plant growth and improving soil and preparation method thereof
CN118754788A
Formula and preparation process of macroelement water-soluble fertilizer based on Gobi region
CN119100879A
Cited By
Preparation method of humic acid-containing water-soluble organic fertilizer with chelated medium trace elements for synergism
CN120647468A
Preparation method of nutrient-rich biological culture medium
CN120827079A
Water-soluble biochar base fertilizer
CN121248361A
Method for improving nitrogen utilization rate of eucalyptus
CN121369147A
A method of increasing nitrogen use efficiency in eucalyptus
CN121369147B